Eating Bitterness : New Perspectives on China's Great Leap Forward and Famine - Manning, Kimberley Ens, 1970-; Wemheuer, Felix (Book collections on Project MUSE., 2011)
When the Chinese Communist Party came to power in 1949, Mao Zedong declared that "not even one person shall die of hunger." Yet some 30 million peasants died of starvation and exhaustion during the Great Leap Forward. Eating Bitterness reveals how men and women in rural and urban settings, from the provincial level to the grassroots, experienced the changes brought on by the party leaders' stumbled attempts to modernize China. This landmark volume lifts the curtain of party propaganda to expose the suffering of citizens and the deeply-contested nature of state-society relations in Maoist China.